Omicron subvariant BA.5 is highly contagious but containable: Successful experience from Macau - Xu, Cong; Wang, Jue; Yu, Lili; Sui, Xinbing; Wu, Qibiao (Frontiers in Public Health, 2023)
Introduction Due to its high transmissibility and immune escape, Omicron subvariant BA.5 has become the dominant strain of the SARS-CoV-2 virus and led to escalating COVID-19 cases, how to cope with it becomes an urgent issue. A BA.5 infection surge burst out on 18 June 2022 and brought an unprecedented challenge to Macau, the most densely populated region worldwide. This study aimed to analyze the characteristics of this outbreak and summarize the useful anti-epidemic measures and experiences during this outbreak. Methods All data were obtained from the Government Portal of Macao SAR (https://www.gov.mo), and the Special Webpage Against Epidemics, the Macao Health Bureau (www.ssm.gov.mo). An epidemiologic study was performed to analyze epidemic outcomes, including the infection rate, the proportion of symptomatic cases, the case fatality ratio (CFR), etc. Data were analyzed using SPSS Version 20. A p-value <0.05 was considered statistically significant. The anti-epidemic measures and experience were reviewed and summarized. Results The BA.5 outbreak resulted in 1,821 new cases, which was significantly more than the cumulative cases of the previous variants of COVID-19 in Macau. The symptomatic cases accounted for 38.71% of the total cases, which was higher than that of the previous variants. After 6-week concerted efforts, Macau effectively controlled the outbreak, with an infection rate of 0.27%, which was much lower than many BA.5-attacked regions. The CFR was approximately 0.86%, which was not statistically different from that of previous variants. Six victims were chronically ill senior elders and their vaccination rate was much lower than the average level. Macau took a comprehensive anti-epidemic strategy to win a quick victory against BA.5, especially the “relatively static” strategy that was first formulated and applied by Macau for the management of the COVID-19 pandemic. Successful experience showed that although BA.5 was highly contagious, it could be contained by comprehensive anti-epidemic measures, including adequate anti-epidemic preparation, herd immunity through vaccination, repeated mass nucleic acid tests and rapid antigen tests, KN-95 mask mandate, the “relatively static” strategy, precise prevention and control, epidemiological investigation and tracing, and traditional Chinese medicine treatment, etc. Discussion In Macau, compared with the previous subvariants, BA.5 is associated with increased transmissibility and a higher proportion of symptomatic cases, however, the risk of death remains similar, and the infection rate is much lower than that in many other BA.5-attacked regions. BA.5 is highly contagious but still containable, Macau's experience may offer hints for the regions experiencing the BA.5 waves to choose or adjust a more rational anti-epidemic strategy.